Attention, coordination and bounded recall - Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2014)
I consider a flexible framework of strategic interactions under incomplete information in which, prior to committing their actions (consumption, production, or investment decisions), agents choose the attention to allocate to an arbitrarily large number of information sources about the primitive events that are responsible for the incompleteness of information (the exogenous fundamentals). The analysis sheds light on what type of payoff interdependencies contribute to inefficiency in the allocation of attention. The results for the case of perfect recall (in which the agents remember the influence of each source on their posterior beliefs) are compared to those for the case of bounded recall (in which posterior beliefs about the underlying fundamentals are consistent with Bayesian updating, but in which the agents are unable to keep track of the influence of individual sources on their posterior beliefs).
Keywords: C72; D62; D83; E50; 330; endogenous information; strategic complementarity/substitutability; externalities; efficiency; welfare; bounded recall